(3LRA ajg caGjI GdeJYHO hJMaI GdeJRgOs - (3YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, CHh eMeO, Rcj GdOjf GdefPQj ,J (B656 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdGeGe GdMeO ddg Gdehab dUGdM GdCYeGd hHYO aEf CNj CMeO YHO GdcQje fgL Gddg Hg GdfgL Gdbhje hUQa Yfg GdTjWGf GdQLje SCdfi Cf CLeY dg cJGHkG s
(3BNQgG (B:s
(3HGH ai Cf ai GdLfI HGHkG jONd efg GdeJUObhf , hHg MOKfG CHh CMeO eMeO Hf GHQGgje Cf GHG gQjQI bGd SeYJ QShd Gddg jbhd (B: (3ddLfI YTQI CHhGH s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3Ydjg bQGAI hSeGY Ydi GdeNQLs
(3Z(B/ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B30s
Keywords: (3eJaQbGJs